Student engagement with a content-based learning design - Brenda Cecilia Padilla Rodriguez; Alejandro Armellini (Association for Learning Technology, 2013)
While learning is commonly conceptualised as a social, collaborative process in organisations, online courses often provide limited opportunities for communication between people. How do students engage with content-based courses? How do they find answers to their questions? How do they achieve the learning outcomes? This paper aims to answer these questions by focusing on students’ experiences in an online content-based course delivered in a large Mexican organisation. Sales supervisors (n=47) participated as students. Four main data sources were used to evaluate engagement with and learning from the course: surveys (n=40), think-aloud sessions (n=8), activity logs (n=47) and exams (n=43). Findings suggest that: (1) Students engage with a content-based course by following the guidance available and attempting to make the materials relevant to their own context. (2) Students are resourceful when trying to find support. If the materials do not provide the answers to their questions, they search for alternatives such as colleagues to talk to. (3) Content-based online learning designs may be engaging and effective. However, broadening the range of support options available to students may derive in more meaningful, contextualised and rewarding learning experiences.